Rietveld Analysis on X-Ray Diffraction Of South Kalimantan Kaolin Clays - Febrianti, Rulliana; Herlina, Firda; Saukani, Muhammad (Berkala Ilmiah Pendidikan Fisika, 2018)
At least 13 million tons of kaolin claystone lie in several regencies of South Kalimantan covering Banjar, Tapin, Hulu Sungai Utara and Kotabaru regencies. This paper reports an attempt to explore their crystalline state characteristics, projecting their potential use for geopolymer. Sungai Tabuk, Cintapuri and Tatakan, due to their largest kaolin claystone deposits, were chosen as the sampling sites. The kaolin samples were prepared by syphoning method prior to X-ray diffraction (XRD) characterizations in determining their crystalline phases. XâPert HighScore Plus and Rietica software were respectively responsible for the qualitative and quantitative phase analyses. The qualitative analysis used search and match method at peak position and peak height between measured and calculated diffraction patterns. Our study revealed the existence of two main phases in the sample, i.e. quartz (SiO2) and kaolinite (Al2Si2O5(OH)4). In addition, the Quantitative analysis used the Rietveld method with the least squares method approach. Rietveld refinement was based on a goodness of fit score of less than 4% by minimizing the difference in the character of the diffraction pattern (position, height, width and peak shape) between the observed and the calculated XRD patterns. The Rietveld quantitative analysis shows, Tatakan is an area with kaolinite-richest deposit (Â±84%), followed by Cintapuri (Â±76%) and Tabuk (Â±70%); quartz is found in reverse.